Al-Qur’an Sebagai Syifa’ dan Meditasi Kesehatan - Siti Hajar; riza Awal Novanto (AL-MUFASSIR, 2021)
The Qur'an is the word of God which is full of miracles, and will always be in accordance with the times and times (shâlihun likulli zamân wa al makân). Muslims should use the Qur’an as a solution to every problem they face and are constantly changing, considering that the Koran is easy to understand and live up to and all things are summarized in the Koran. There are so many miracles that the Qur'an possesses, including that the Qur'an is a medicine (syifâ) or an antidote and an antidote to all kinds of diseases, both spiritual and physical, including as an antidote to jinn, devils or magic. How the Koran becomes a panacea for every disease and how to meditate with the Koran where meditation is known in Chinese medicine as a way to relieve pain.